Effect of Cutting off Power to the Hatcher on the Quality of Chicks - Ávila, Frank; Nieto Pico, Javier Eduardo; Vargas Bayona, Javier Enrique (Spei Domus, 2013)
The study aimed to evaluate chick quality when the tempera‑ture was changed at the end of the incubation cycle. The experiment was performed on a single machine hatcher (chick master®, genesis III), with a capacity for births of as many as 15,552 chickens. There were 3 trials: in the first one, power was turned off to the hatcher machine 48 hours before birth; for the second trial it was turned off 24 hours prior to birth; finally, for the third trial power was not turned off. The same batch of Cobb‑Avian 48 egg layers ages 32 and 33 weeks was used. The percentage of navel healing was assessed for the first chicks, second chicks along with the discard percentage and dehydration percentage. In carrying out embryo diagnosis, late mortality and unborn chicks were taken into account. Statistical analysis was descriptive for each variable and was based on the Cervantes physical examination test performed on the hatched chicks. In the first trial, navel healing was 93.8% in first chicks, 0.5% in second chicks and 0.5% among discards. In the second trial, navel heal‑ing was 94.2% in first chicks, 0.4% in second chicks and 0.7% among discards. In the third trial, the figures were 92.9% among first chicks, 0.7% among second chicks and 0.6% among discards. It was found that when the power was always on, there was dehydration among 8% of the animals and a 0.2% increase in late mortality along with 0.6% in bad positions with signs of heat stress.
Keywords: dehydration; embryo‑diagnosis; navels; birth rate; temperature